Karyotype differentiation between Koelreuteria bipinnata and K. elegans subsp. formosana (Sapindaceae) based on chromosome banding patterns. - Urdampilleta, Juan Domingo (2005)
Koelreuteria Laxm., a genus in the tribe Koelreuterieae (Sapindaceae), includes three tree species that are widely recognized as having horticultural merit. The two more closely related species, K. bipinnata Franch. and K. elegans (Seem.) A. C. Sm., are easily distinguished from K. paniculata Laxm. by their bipinnate leaves. In this study, both species were investigated cytogenetically and their karyotypes and heterochromatic patterns were compared. Koelreuteria bipinnata and K. elegans ssp. formosana (Hayata) F. G. Mey. both have 2n = 32 but their karyotypes present slight morphological differences when observed using conventional staining. Chromosome banding patterns are reported for the first time for this genus. Both species exhibit terminal heterochromatic blocks, as revealed by C-Giemsa and C-CMA3, but the band size varies between the species. Koelreuteria bipinnata has larger heterochromatic blocks and more GC-rich segments, while in K. elegans ssp. formosana these bands are smaller. The relationship between the karyotype features in these closely related species is discussed. © 2005 The Linnean Society of London, Botanical Journal of the Linnean Society, 2005, 149, 451–455.